PENGARUH CELEBRITY ENDORSEMENT CREDIBILITY TERHADAP CONSUMER BASED BRAND EQUITY DAN BRAND CREDIBILITY SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PENGIRIMAN LOGISTIC J&T EXPRESS - KENDY MAHARIJAYA PURNAMA (Jurnal Strategi Pemasaran, 2018)
The increasingly endorsement of Celebrities, especially in the field of marketing has resulted in logistics companies in Indonesia to endorsement as the main attraction to attract consumers. Selection Celebrities as endorser also must be based on what is in accordance with what is wanted by company. Because Celebrities who become endorsers greatly affect the credibility of the products that are advertised right by the Celebrity. The problem that occurs is how Celebrity Endorsement Credibility can affect Consumer Based Brand Equity and Brand Credibility to deliver goods by using J & T Express This research will be carried out by distributing questionnaires to 100 respondents who have done J & T Express with PLS analytical technique where the research result can show the influence of Celebrity Endorsement Credibility used by J & T Express to Consumer Based Brand Equity and Brand Credibility.